1995
DOI: 10.1016/s0886-3350(13)80563-9
|View full text |Cite
|
Sign up to set email alerts
|

Drop, then decide approach to topical anesthesia

Abstract: I developed an approach to topical anesthesia--drop, then decide--with the goal of increasing the percentage of patients able to have topical anesthesia for anterior segment surgery. This study comprised 150 consecutive surgeries performed using the technique, including cataract extraction with intraocular lens (IOL) implantation, trabeculectomy, combined procedures, and McCannel suturing. Six patients also had anterior vitrectomy. Patients were not preselected. All cases were initiated with topical anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…29,30 Martini et al 12 showed that topical ropivacaine is safe in endothelial toxicity and seemed to be a good alternative to lidocaine, but could cause transient corneal oedema. None of our patients in the ropivacaine group displayed any kind of corneal oedema.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Martini et al 12 showed that topical ropivacaine is safe in endothelial toxicity and seemed to be a good alternative to lidocaine, but could cause transient corneal oedema. None of our patients in the ropivacaine group displayed any kind of corneal oedema.…”
Section: Discussionmentioning
confidence: 99%
“…This method avoids the risks associated with peribulbar, subtenonal or retrobulbar anaesthesia, such as periocular bruising or swelling, ptosis, optic nerve injury, orbital haemorrhage, central retinal artery or vein occlusion, brain-stem anaesthesia and even death (Petersen & Yanoff 1992). In addition, because the eye is left unpatched, postoperative visual recovery is immediate and ocular motility normal (Dinsmore 1995;Tranos & Peter 2006). Analysis of the data demonstrates that combined topical and subconjunctival anaesthesia is a technique that is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…As estatísticas não são uniformes e variam de acordo com os cirurgiões (23)(24)(25) . Neste estudo, pela microscopia de luz, não foram encontradas alterações morfológicas na retina de coelhos albinos, quando foi utilizada a injeção intravítrea de lidocaína a 0,5%, 1 % e 2%, coincidindo com os achados de Zemel et al (6) , Lincoff et al (22) e Nishide et al (26) .…”
Section: Discussionunclassified